2021
DOI: 10.1172/jci146323
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix protein laminin β1 regulates pain sensitivity and anxiodepression-like behaviors in mice

Abstract: Patients with neuropathic pain often experience comorbid psychiatric disorders. Cellular plasticity in the anterior cingulate cortex (ACC) is assumed as a critical interface for pain perception and emotion. However, substantial efforts thus far are focused on intracellular mechanisms of plasticity rather than extracellular alterations that might trigger and facilitate intracellular changes.Laminin is a key element of extracellular matrix (ECM) consisting of one -, and -chain and implicated in several pathop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 85 publications
(119 reference statements)
1
31
0
Order By: Relevance
“…We next sought to identify transcriptional changes that may contribute to the development of depressive symptoms induced by neuropathic pain. Previous studies have reported transcriptomic changes in the brains after SNI but at much later time points (2.5–6 months post-surgery) ( Alvarado et al, 2013 ; Berta et al, 2017 ; Descalzi et al, 2017 ; Li et al, 2021 ). Since the mPFC and the ACC are two brain regions critical for regulating both the affective symptoms of neuropathic pain and depression ( Bliss et al, 2016 ; Descalzi et al, 2017 ; Li et al, 2021 ; Tan and Kuner, 2021 ), we chose to examine the transcriptomic profiles of the mPFC and the ACC at 2 weeks post-SNI, a time point when the mice started to show mild depressive phenotypes, to identify the potential molecular signatures that are involved in the emergence of depressive phenotypes during the progression of neuropathic pain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next sought to identify transcriptional changes that may contribute to the development of depressive symptoms induced by neuropathic pain. Previous studies have reported transcriptomic changes in the brains after SNI but at much later time points (2.5–6 months post-surgery) ( Alvarado et al, 2013 ; Berta et al, 2017 ; Descalzi et al, 2017 ; Li et al, 2021 ). Since the mPFC and the ACC are two brain regions critical for regulating both the affective symptoms of neuropathic pain and depression ( Bliss et al, 2016 ; Descalzi et al, 2017 ; Li et al, 2021 ; Tan and Kuner, 2021 ), we chose to examine the transcriptomic profiles of the mPFC and the ACC at 2 weeks post-SNI, a time point when the mice started to show mild depressive phenotypes, to identify the potential molecular signatures that are involved in the emergence of depressive phenotypes during the progression of neuropathic pain.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of matrix metalloproteases-9 and matrix metalloproteases-2 by pharmacological or siRNA-based strategies effectively produced anti-allodynic effect ( Kawasaki et al, 2008 ). Li et al (2021) reported that SNI reduced the expression of LAMB1, a major component of extracellular matrix in the ACC. Knockdown of LAMB1 in the ACC increased the release probability of neurotransmitters and led to abnormal postsynaptic spine remodeling, which in turn increased pain sensitivity and caused depression-like behaviors ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in the levels of proinflammatory cytokines [184,185] and a decrease in the levels of neurotrophins [186,187] are related to emotional disorders. ACC, the first-order cortical region that responds to painful stimuli [188], plays an important role in pain information processing [189][190][191], including the processing of pain affection [192][193][194][195]. Abnormal expression of TNF-α, neuronal hyperexcitability and microglial activation in ACC contribute to inflammatory and neuropathic pain and pain aversion [20,196].…”
Section: Tnf-α/necroptosis In Pain-associated Anxiety and Depressionmentioning
confidence: 99%